2008
DOI: 10.1103/physrevlett.100.168104
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Elasticity

Abstract: With a model that incorporates hydrodynamics directly, we show that flow experiments can be used for detecting some characteristics of the DNA elasticity which manifest themselves clearly at large length scales but cannot be observed by mechanical forcing experiments even at very small length scales. By systematic analysis, the conclusiveness of different experimental methods is evaluated. For the wormlike chain, confirmed as the correct model for DNA, we find an underlying scaling relation between its extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…The dotted magenta curves are the analytical ones for an infinite system length, obtained by using Eqs. (3), (9a), and (21), while all the other curves are for finite system sizes which gradually match the analytical curve as N becomes larger. x shows a finite discontinuity at a critical g sc = 1.18.…”
Section: Elastic Constantsupporting
confidence: 61%
“…The dotted magenta curves are the analytical ones for an infinite system length, obtained by using Eqs. (3), (9a), and (21), while all the other curves are for finite system sizes which gradually match the analytical curve as N becomes larger. x shows a finite discontinuity at a critical g sc = 1.18.…”
Section: Elastic Constantsupporting
confidence: 61%
“…Correspondence to a specific polymer may be adjusted by using the semi-flexible worm-like chain (WLC) model. It has been shown that in free space neither entropic nor intrinsic parts of elasticity differ appreciably for FC and WLC models [30]. In this article we aim to study the general properties of the process.…”
Section: Relating the Model To Real-world Translocation Processesmentioning
confidence: 99%
“…We apply no bending potential, rendering the polymer as a freely-jointed chain (FJC), instead of a worm-like chain (WLC). We have previously shown that the difference of the two models when simulating polymer elasticity in mechanical stretching or in flow is insignificant [13].…”
Section: A the Polymer Modelmentioning
confidence: 99%